Characterization and treatment of textile wastewater - Patel, Himanshu; Vashi, R. T. (Waltham, MA : Butterworth-Heinemann is an imprint of Elsevier, 2015)
Characterization and Treatment of Textile Wastewater covers fundamental knowledge of characterization of textile wastewater and adsorbents; naturally prepared adsorption and coagulation process for removal of COD, BOD and color. This book is intended for everyone actively working on the environment, especially for researchers in textile wastewater, as the problem of disposal of textile influent is worldwide. Potential technical environmental persons like engineers, project managers, consultants, and water analysts will find this book immediately useful for fine-tuning performance and reliabil.
Calculation2.2.14. Phosphate; Interferences and limitations; Principle; Apparatuses; Reagents; Actual process; Polyphosphate; Calculation; 2.2.15. Silica; Precautions; Principle; Reagents; Actual process; 2.2.16. Sodium; Principle; Pretreatment; Reagents; Actual process; 2.2.17. Heavy metals (Cu, Pb, Mn, and Cd); Principle; Pretreatment; Reagents; Actual process; 2.3. Characterization; 2.3.1. Results; 2.3.2. Discussion; References; Chapter 3: Feasibility of Naturally Prepared Adsorbent; List of Figures; List of Tables; 3.1. Introduction; 3.1.1. Adsorption isotherm for batch treatment.
Online resource; title from PDF title page (Ebsco, viewed June 3, 2015).
Includes bibliographical references and index.
Keywords: Textile industry -- Environmental aspects; Sewage -- Purification; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; TECHNOLOGY & ENGINEERING -- Textiles & Polymers; Sewage -- Purification; Textile industry -- Environmental aspects; Electronic books